ANALISIS TINGKAT KESEHATAN BANK (PENDEKATAN RGEC) PADA BANK RAKYAT INDONESIA 2013-2015 - Putri, Ratna Lutfiani; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out the health level of Bank Rakyat Indonesia Persero Tbk in 2013-2015 periods which is reviewed simultaneously from aspects i.e. Risk Profile, Good Corporate Governance, Earnings, Capital, and RGEC. The data analysis method has been done by using the bank health analysis with risk approach (Risk-based Bank Rating) which includes the assessment of the RGEC factors. The result of the research at PT Bank Rakyat Indonesia Persero Tbk in 2013 period shows that the Bank is very healthy, it is shown by Risk Profile aspect which includes the NPL ratio of 1,26% and the LDR is 88,54%. Earnings aspect includes 4,74% ROA and NIM 7,94%. Capital aspect includes CAR 15,25%. The 2014 period shows that the Bank is very healthy and it is shown by Risk Profile aspect which includes the NPL Ratio 1,26% and the LDR 81,75%. Earnings aspect includes ROA 4,31% and NIM 12,24%. Capital aspect includes the CAR ratio 13,49%. And the 2015 period shows that the Bank is very healthy, it is shown by Risk Profile aspect which includes the NPL ratio 1,26% and the LDR 81,75%. Earnings aspect includes ROA 4,31% and NIM 12,24%.Keywords: Bank Health Level, CAMEL, CAMELS, RGEC